Chinese secondary school students' conceptions of assessment and achievement emotions: endorsed purposes lead to positive and negative feelings. Issue 1 (2nd January 2018) - Chen, Junjun; Brown, Gavin T. L.
Abstract: Student perceptions of the purposes of assessment have been shown to be significant predictors of self-regulated learning. Their relationship to achievement emotions is less well understood. This paper reports a survey study of Chinese middle and high school students ( N = 1, 393) self-reported conceptions of the purpose of assessment and their achievement emotions using inventories with previously developed Chinese versions. While pre-existing models were not replicated, exploratory techniques developed well-fitting measurement models for each inventory and a structural equation model showed that significant variance in achievement emotions was elicited by certain beliefs about assessment. Positive emotions of pride and enjoyment depended primarily on conceptions that assessment (1) contributed to student moral and skill development, (2) was accurate, and (3) was not for evaluating schools or teachers. Negative emotions of anger and shame depended primarily on conceptions that assessment was (1) for evaluating schools and teachers and (2) not for improving teaching and learning. Thus, student emotional responses to assessment in China logically depend on beliefs that assessment reliably relates to developing their own learning, skills, and moral character.